On the use of dynamically varied loudspeaker spacing in wave field synthesis - Ranjan, Rishabh (2015)
Wave field synthesis (WFS) has evolved as a promising spatial audio rendering technique in recent years and has been widely accepted as the optimal way of sound reproduction technique. Suppressing spatial aliasing artifacts and accurate reproduction of sound field remain the focal points of research in WFS over the recent years. The use of optimum loudspeaker configuration is necessary to achieve perceptually correct sound field in the listening space. In this paper we analyze the performance of dynamically spaced loudspeaker arrays whose spacing varies with the audio signal frequency content. The proposed technique optimizes the usage of a prearranged set of loudspeaker arrays to avoid spatial aliasing at relatively low frequencies as compared to uniformly fixed array spacing in conventional WFS setups.